Dipeptide and xanthones from Artocarpus kemando Miq. - Mohd Hashim, Najihah; Rahmani, Mawardi; Shamaun, Shireen Shaharina; Ee, Gwendoline Cheng Lian; Md. Sukari, Mohd Aspollah; Ali, Abdul Manaf; Go, Rusea (Academic Journals, 2011)
The ground air-dried stem bark of Artocarpus kemando Miq. (Moraceae) collected from Sarawak, Malaysia was subjected to sequential extraction with hexane, chloroform and methanol to give three crude extracts. Silica gel chromatographic separation of the chloroform extract yielded a dipeptide, aurantiamide benzoate, cycloartobiloxanthone, dihydroartoindonesianin C and 6,7-dimethoxycoumarin. All compounds were obtained as crystals and their structures were determined on the basis of spectroscopic data, including UV, IR, MS, 1D- and 2D-NMR and comparison with known related compounds. This is the first report on the identification of a peptide in Artocarpus species.